If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-3w+6=-5w-12
We move all terms to the left:
-3w+6-(-5w-12)=0
We get rid of parentheses
-3w+5w+12+6=0
We add all the numbers together, and all the variables
2w+18=0
We move all terms containing w to the left, all other terms to the right
2w=-18
w=-18/2
w=-9
| -352=4(-7x+16) | | 31=3x+5x+7 | | (3x−1)+6x=13 | | 8x −37=−5 | | -8w+9=-6w+3 | | {k}{5}-3=12 | | 7x-25=2x+30 | | 30.50=4.50x+3.50 | | 29=u/3-16 | | 8v+3((1)/(3)v-6)=9v+2v+12 | | 4+4x=4x+5 | | 0.2=1,200,000-c/1,200,000 | | 3w+15-5+2=5 | | -8y-36=-4(y+2) | | -4x+7-3x=-49 | | 6/x+7=3 | | -6(m-5)=-9(m-6) | | 5f=5f-10 | | -2-2g=-g | | 9+3=-4(6x-3) | | 9(x+3)-7x=-3 | | 217=7(-6n+1) | | 6x+13=3x−1 | | 4x-29=113 | | 8a-7+5a=2a-3 | | 3x2+36x+96=0 | | -20n=400 | | 2a=4=7+a | | 12m+32=8 | | 8x+3=97 | | 8u-5=-9+9u | | 6n-10=6(-3n+3)-4(7-6n) |